Vaccination Control in a Stochastic SVIR Epidemic Model. (24th May 2015) - Witbooi, Peter J.; Muller, Grant E.; Van Schalkwyk, Garth J.
Abstract : For a stochastic differential equation SVIR epidemic model with vaccination, we prove almost sure exponential stability of the disease-free equilibrium forR 0 < 1, whereR 0 denotes the basic reproduction number of the underlying deterministic model. We study an optimal control problem for the stochastic model as well as for the underlying deterministic model. In order to solve the stochastic problem numerically, we use an approximation based on the solution of the deterministic model.